DO INNOVATIVE WORK BEHAVIOR AND ORGANIZATIONAL COMMITMENT CREATE BUSINESS PERFORMANCE: A LITERATURE REVIEW - Lili Fadli Muhamad; Rizal Bakti; Mohamad Trio Febriyantoro; Kraugusteeliana Kraugusteeliana; Abu Muna Almaududi Ausat (Universitas Pahlawan Tuanku Tambusai, 2023)
Nowadays, there are many new knowledge, innovations, and changes marked by the rapid advancement of technology. Business competition is becoming increasingly competitive. This research will explain two important constructs that can create increased business performance and remain adaptive, namely innovative work behavior and organizational commitment. This condition is very crucial, considering that many business organizations neglect to produce innovative employees and build solid organizational commitment, thus marked by layoffs. The literature review method is used in this study in order to find complete and complementary results. Based on the literature review, this study arrived at the finding that innovative work behavior and organizational commitment can create successful business performance such as increased sales, profits, satisfaction, market share, high productivity, employee loyalty, and low employee turnover. Such indicators are good assets for companies to remain agile in improvising in an increasingly modern era in implementing business strategies. The results of this study are expected to be discussed in management science and business administration, and implemented for certain parties in order to achieve business success.